Psychodynamic Features of Depressed Patients with Dependent Personality Disorder and Hypokalemia: a Case Report - Jaya, Muhammad Alim; Syahrir, Andi Karlina (Action Research Literate, 2024)
Depression is one of the most common mental disorders in society. Depression is influenced by several factors, including the personality of the sufferer and the existence of a comorbid disease that aggravates the symptoms. Several previous studies have not clearly reported on the psychodynamic picture of depressed patients with dependent personality disorder accompanied by hypokalemia. The study aims to provide a psychodynamic picture of depressed patients with dependent personality disorder accompanied by hypokalemia. A man, 26 years old, an Indonesian citizen, came with the main complaint of feeling helpless to do anything that has been burdensome for the last 2 months. The complaint was felt to be aggravating after he started working as a private employee. The patient feels insecure in his ability to complete the work assigned to him and feels that he is looked down upon by his peers and superiors. Patients often miss the figure of their deceased father. In addition, the patient has suffered from hypokalemia since he was in high school and has taken potassium supplements until now. The symptoms of depression experienced by patients are aggravated by the presence of dependent personality disorders and hypokalemia suffered by patients. Dependent personality disorder lowers the patient's confidence, and hypokalemia aggravates the vegetative symptoms he experiences, such as body weakness, decreased appetite, and palpitations. Dependent personality disorder and hypokalemia are very influential in aggravating the clinical symptoms experienced by depressed patients